CO2-saturated brine injection into heavy oil carbonate reservoirs: Investigation of enhanced oil recovery and carbon storage - Salehpour, Mohammad; Riazi, Masoud; Malayeri, M. Reza; Seyyedi, Mojtaba (Journal of petroleum science & engineering, 2020)
Fossil fuel to a large extent is still expected to dominate the global energy demands for the next few decades. An inevitable and detrimental consequence of such source of energy is though the emission of hazardous CO2. Therefore, technologies that can utilize and permanently store the emitted CO2 are of great interest for the energy industry. A viable large-scale CO2 utilization and storage technology is the CO2 enhanced oil recovery (EOR) technique. However, this technique mostly lacks a good volumetric sweep efficiency at the reservoir-scale. An alternative option is CO2-saturated (carbonated) water injection (CWI). Although the oil recovery and CO2 storage potential of CWI for light and medium crude oil systems have been extensively studied, only a few studies investigated carbon storage particularly in heavy oil reservoirs. As such, this study through an experimental approach provides more insights into this subject. The results show that the high asphaltene contents of the used heavy crude oil led to formation of in-situ water-in-oil emulsions during both waterflooding and CWI. Emulsions decreased the flow path area of injection fluid and blocked some pores and throats, which consequently led to local flow diversions to un-swept areas of the porous media and an improvement in oil recovery. The emulsion-induced local flow diversions during CWI improved the effectiveness of oil recovery mechanisms of CWI by bringing more residual oil in contact with carbonated brine. Both secondary and tertiary CWI led to 24% and 20% higher oil recovery compared to conventional waterflooding, respectively. Furthermore, during secondary and tertiary CWI around 22% and 32% of the total injected CO2 were stored in the core plugs mostly by solubility trapping in the residual oil. The CO2 utilization factor increased over the carbonated brine injection period indicating higher CO2 needs to be injected for producing a barrel of oil. •CO2-saturated water injection is a promising option for heavy oil recovery.•Carbonated water injection is a feasible method for CO2 storage.•Water-in-oil emulsion formation leads to additional oil recovery.•Water-in-oil emulsions improve the performance of carbonated water injection.•The average amount of required CO2 for producing a barrel of increases by time.